Promoting Yield and Oyster Mushroom Cycle Production by Using Date Kernel and Wheat Straw Mixture as a Cultivation Substrate - Ghada Lamraoui; Choukri Tefiani; Asma Maouedj; Abdelmalek Chaalel; Nerdjes Spiga; Diego Cunha Zied; Salim Rouar; Kab-Yeul Jang; Fehmi Boufahja; Walid Elfalleh; Hamdi Bendif (BioResources)
Mushroom production can contribute to food security through producing food of high nutritional value and medicinal interest. This study examined the effectiveness of using date kernel (K) in a mixture with wheat straw (WS) as substrate on yield and different crop stages duration for Pleurotus ostreatus (P.O) cultivation. Five substrate formulas were investigated using K and WS, alone and in combination. The results indicated that there was a significant difference between formulas. Using wastes separately showed the lowest yield, whereas the substrate with 25% K gave the highest total yield (478 g) and biological efficiency (BE) of 95.61%, in 223 d and 78.52% as BE of three first flushes in 110.8 d. substrate with 75% K was more effective in term of time; it gave in 198.4 d 414 g of mushroom (BE: 82.95%) and 310.6 g (BE: 62.12%) for the three first flushes in 83.2 d. It is more effective to use K and WS in mixture than separately to cultivate P.O., The proportion depends on which we can give up; around 70 g of yield or 26 d as time difference; for more yield in longer time, using 25% K is more suitable, and 75% K is used for shorter time and less yield.